The EndoPredict score predicts response to neoadjuvant chemotherapy and neoendocrine therapy in hormone receptor-positive, human epidermal growth factor receptor 2-negative breast cancer patients from the ABCSG-34 trial. (July 2020) - Dubsky, Peter C.; Singer, Christian F.; Egle, Daniel; Wette, Viktor; Petru, Edgar; Balic, Marija; Pichler, Angelika; Greil, Richard; Petzer, Andreas L.; Bago-Horvath, Zsuzsanna; Fesl, Christian; Meek, Stephanie M.; et al.
Abstract: Background: Neoadjuvant chemotherapy (NaCT) and neoadjuvant endocrine therapy (NET) can reduce pre-operative tumour burden in patients with estrogen receptor (ER)-positive, human epidermal growth factor receptor 2 (HER2)-negative early-stage breast cancer. This prospective translational study assessed the ability of a 12-gene molecular score (MS; EndoPredict®) to predict response to NaCT or NET within the ABCSG-34 trial. Patients and methods: Hormone receptor (HR)-positive, HER2-negative samples from patients in the ABCSG-34 randomized phase II trial were selected and EndoPredict testing was performed to generate a 12-gene MS. ABCSG-34 patients were assigned to receive either NaCT or NET based on menopausal status, HR expression, grade and Ki67. Response was measured by residual cancer burden (RCB). Results: Patients selected for NaCT generally had high-risk disease by 12-gene MS (125/134), while slightly more patients treated with NET had low-risk disease (44/83). Low-risk NaCT-treated and high-risk NET-treated tumours responded poorly (NPV 100% [95% CI 66.4%–100%] and NPV 92.3% [95% CI 79.1%–98.4%], respectively]. The 12-gene MS significantly predicted treatment response for NaCT (AUC 0.736 [95% CI 0.63–0.84]) and NET (AUC 0.726 [95% CI 0.60–0.85]). Conclusions: The 12-gene MS predicted RCB after treatment with neoadjuvant therapies for patients with HR-positive, HER2-negative early-stage breast cancer. Tumours with low MS were unlikely to benefit from NaCT, whereas a high MS predicted resistance to NET. This additional biologic information can aid personalized treatment selection in daily practice and builds a strong rationale to use EndoPredict in biomarker-driven studies in the neoadjuvant setting. Highlights: A 12-gene molecular score predicted response to pre-operative neoadjuvant therapy. Low-score breast tumours were unlikely to respond to neoadjuvant chemotherapy. Breast tumours with high scores were resistant to neoadjuvant endocrine therapy.